Label-free relative quantitative proteomics reveals extracellular vesicles as a vehicle for Salmonella effector protein delivery - Wu, Tao; Zhang, Biao; Lu, Juane; Huang, Ailin; Wu, Hao; Qiao, Jianjun; Ruan, Haihua (Frontiers in Microbiology, 2022)
Extracellular vesicles are small vesicles with a diameter of 30-150 nm that are actively secreted by eukaryotic cells and play important roles in intercellular communication, immune responses, and tumorigenesis. Previous studies have shown that extracellular vesicles are involved in the process of Salmonella enterica serovar Typhimurium (S. Typhimurium) infection. However, changes in the protein content of extracellular vesicles elicited by S. Typhimurium infection have not been determined. Here, we extracted the extracellular vesicles with high purity from S. Typhimurium-infected Henle-407 cells, a kind of human intestinal epithelial cells, by ultracentrifugation combined with an extracellular vesicles purification kit, and analyzed their protein composition using label-free relative quantitative proteomics. The extracted extracellular vesicles exhibited an oval vesicular structure under electron microscopy, with a mean diameter of 140.4±32.4 nm. The exosomal marker proteins CD9, CD63, and HSP70 were specifically detected. Compared with the uninfected group, nearly 1234 specifically loaded proteins were uncovered in S. Typhimurium-infected Henle-407 cells. Among them were 409 S. Typhimurium-derived specific proteins, indicating a significant alteration in protein composition of extracellular vesicles by S. Typhimurium infection. Notably, these proteins included 75 secretory proteins and over 300 non-secretory proteins of S. Typhimurium, implicating novel pathways for bacterial protein delivery, although it remains unclear if their loading into extracellular vesicles is active or passive. To investigate the roles of these extracellular proteins, we exemplified the function of SopB, a well-known T3SS effector protein, and showed that the extracellular SopB could be taken up by RAW264.7 macrophages, activating the phosphorylation of Akt. This study provides new insights into the mechanism of Salmonella infection through extracellular vesicles that transport virulence proteins to uninfected neighboring cells to facilitate further infection.